Ritual Neduhin Dalam Sistem Pertanian Masyarakat Desa Bunutin, Kecamatan Kintamani, Kabupaten Bangli, Bali - Zarah Afandi, Makhrofsi; Arjani, Ni Luh; Kaler, I Ketut (Humanis; Vol 21 No 1 (2017)DO - 10.24843/JH.2017.v21.i01.p07, 2017)
Bunutin village is one of the Bali Aga villages located in Kintamani, Bali which still maintaind traditional ceremony. One of the traditional ceremonies still preserved by the Bunutin community is the Neduhin ceremony. Neduhin ceremony is a routine ritual performed by the people of Bunutin Village once every year. The aims of this research are to know: (1) Why Neduhin Ritual is implemented by the Community in Bunutin Village (2) How is the Implementation Stage of Neduhin Ritual (3) How to Function and Meaning of Neduhin ceremony in Agricultural System of Bunutin Village Community. The theory used in this research is the theory of B. Malinowski on the function of culture, the theory of E. B Tylor about religion, as well as the manifest and latent theory by Robert K. Merton. The concepts used in this research are Neduhin ceremony, Agricultural System, and Bunutin Village Community. The results revealed that the reason for the implementation of the Neduhin ceremony by the community of Bunutin Village was the ritual of apologizing to Ida Betara for causing him to be angry, so that the village of Bunutin experienced catastrophes such as crop failure in their fields. The Neduhin ceremony procession consists of three stages: The phase I (preparation of neduhin) consists of the Neratas and the Ngusaba Toya ritual. The phase II (ritual stage of neduhin) consists of the mendak tirtha by teruna, nuwur Ida Betara Kawitan, nuwur Iratu ring Pura Panti, nuwur Iratu Ida Betara Mulu Mideh, and megibung tradition by krama desa. Ritual phase III (ritual performed after neduhin) is a procession of Ngodog lidi tradition. In Neduhin ceremony there are latent and manifest functions. In addition, as for the meaning contained in the Neduhin is a religion, an education, and a welfare.